Edukasi Manajemen Pemasaran Digital bagi Masyarakat Desa Krobokan, Juwangi dalam Upaya Penguatan Penjualan Online - Mukti Ali Syaifuddin Putra Prasetya; Rima Maya Siva Kafi; Luthfia Nurul Azizah; Fanka Aulia; Alean Kistiani Hegy Suryana (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
This service examines the use of the social media platform of the tiktok application which acts as an effort to approach digital promotion for micro, small and medium enterprises in Krobokan village, Juwangi. Although MSMEs allocate an important role in sales products to the community, they do not fully understand digital media.This service applies a qualitative method by conducting interviews and socialization to the community which amounts to around 30 people consisting of 10 MSME business actors. The results of the interview identified MSME actors in Krobokan village who are not fully aware of the importance of understanding the development of social media as a marketing media tool, therefore we provide education about sales through online media because they only market products traditionally in the village environment. TikTok as a strategic means in supporting sales in today's digital era because the TikTok application is one of the highest platforms that are widely used today such as the TikTok Shop and Live TikTok features in strengthening the introduction of sales to customers through social media. This service concludes that from traditional marketing by word of mouth to marketing in the digital era that focuses on creative digital marketing, efforts have great potential in developing the community's economy in the current digital era.